2016
DOI: 10.1038/srep33437
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing-based analysis of endogenetic fungal communities inhabiting the Chinese Cordyceps reveals unexpectedly high fungal diversity

Abstract: Chinese Cordyceps, known in Chinese as “DongChong XiaCao”, is a parasitic complex of a fungus (Ophiocordyceps sinensis) and a caterpillar. The current study explored the endogenetic fungal communities inhabiting Chinese Cordyceps. Samples were collected from five different geographical regions of Qinghai and Tibet, and the nuclear ribosomal internal transcribed spacer-1 sequences from each sample were obtained using Illumina high-throughput sequencing. The results showed that Ascomycota was the dominant fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
5
39
0
2
Order By: Relevance
“…Previous study revealed that Ophiocordyceps was overwhelmingly dominant in the fruiting bodies and external mycelial cortices of the Chinese Cordyceps, which is consistent with our data. However, in soil samples, Ophiocordyceps, Verticillium, Pseudallescheria, Candida, Ilyonectria, Neonectria and Fusarium were the dominant genera [19]. Another previous study based on HiSeq sequencing of internal transcribed spacer (ITS) genes of soil samples derived from the site that had a high density of Thitarodes larvae and Chinese Cordyceps at Shergyla Mountain revealed that Archaeorhizomyces, Hyphodiscus, Beutheromyces, Pezoloma, Venturia, Geogiossum, Clavulinopsis, Cotylidia, Rammanopsis, Peltigera and Cavana had high relative abundance [28].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous study revealed that Ophiocordyceps was overwhelmingly dominant in the fruiting bodies and external mycelial cortices of the Chinese Cordyceps, which is consistent with our data. However, in soil samples, Ophiocordyceps, Verticillium, Pseudallescheria, Candida, Ilyonectria, Neonectria and Fusarium were the dominant genera [19]. Another previous study based on HiSeq sequencing of internal transcribed spacer (ITS) genes of soil samples derived from the site that had a high density of Thitarodes larvae and Chinese Cordyceps at Shergyla Mountain revealed that Archaeorhizomyces, Hyphodiscus, Beutheromyces, Pezoloma, Venturia, Geogiossum, Clavulinopsis, Cotylidia, Rammanopsis, Peltigera and Cavana had high relative abundance [28].…”
Section: Discussionmentioning
confidence: 90%
“…Although the limited sampling sites covered by this study possibly result in decreasing of credibility of the present results, considerable previous studies support our data and hypothesis. [19,41] As well know, O. sinensis usually occur in the humus-rich horizon of soils. Unfortunately, in present study, we did not determine the characteristics of the soil samples.…”
Section: Discussionmentioning
confidence: 99%
“…For the research of Chinese Cordyceps, more and more investigators focused on their scientific interest in endogenetic fungi of Chinese Cordyceps and the fungal diversity (Zhang et al, 2010;Xia et al, 2015;Xia et al, 2016a;Xia et al, 2016b). Although endogenetic fungi of Chinese Cordyceps had been investigated and studied extensively, there was a little minor fault existing in the research process.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 490 fungal clones were identi ed from the wholecommunity DNA using PCR-single-strand conformation polymorphism (PCR-SSCP) method, 266 of these clones were selected for sequencing and assigned to 21 genera [9]. Three main phyla, including Ascomycota, Basidiomycota, Zygomycota and a notable numbers of unclassi ed Fungi, especially, in the sclerotia and external mycelial cortices were detected by high-throughput 454 sequencing technology [19].…”
Section: Introductionmentioning
confidence: 99%